(3GdJHQ GdeSHhc aj fUjMI Gdedhcs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hgh jNGWH GdSdWGf eMeO Hf edc TGg edc GdTQb hGdZQH s
(3BNQgG (B:s
(3acdeG jfGd GdQLGd ef GdHdGA hGdgdGc hGdeMf aHSHH GdfSGA hGdhaGA efgfi dG jCJi eOi GdCReGf s
(3Cdag ddSWGf eMeO Hf edcTGgs
(3Hg WeS cKjQ COi Edi YOe XghQ GdcdeGJs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
Keywords: (3GdSjGSI hGdGLJeGYs